Students' Perceptions of the Effectiveness of Learning Management During the Covid-19 Period at University - Kusen, Kusen (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study was to analyze student perceptions of the effectiveness of learning management during the covid-19 period at the IAIN Curup Bengkulu Management Program. This research is a type of survey research. The study was conducted in May-June 2022. The population in this study were all undergraduate and postgraduate students of the Islamic Education Management Study Program IAIN Curup. The samples in this study were 73 students who were taken by the purposive sampling technique. The research instrument used is a closed questionnaire which is a modification of the Likert Scale with 4 answer choices. The results of this study indicate that learning management during the covid-19 period in the management program is effective based on student perceptions.